IMPLEMENTASI KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK KONSTRUKSI DI KOTA PALANGKA RAYA - Rudi Waluyo; Novelia Putri Angelica (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2026)
Occupational Safety and Health (OSH) is a critical aspect of the construction industry, as this sector has a high rate of workplace accidents. This study aims to examine the implementation of OSH in construction projects in Palangka Raya, analyze its compliance with applicable regulations, and identify challenges in its implementation. The study was conducted on 8 construction projects, including road, drainage, building, and pile slab projects in Palangka Raya City. The research was carried out over a three-month period, from September to November 2025. The results indicate that OSH implementation has been carried out through the use of Personal Protective Equipment (PPE), the installation of safety signs, the application of an Occupational Safety and Health Management System (OSHMS), risk identification, and the provision of health and emergency facilities. However, implementation remains suboptimal, particularly regarding compliance with PPE usage, consistency in safety activities, and on-site supervision. OSH implementation generally adheres to applicable regulations; however, inconsistencies are still observed in practice. The primary challenges in OSH implementation stem from human factors, the work environment, and project management. Therefore, it is necessary to enhance worker awareness, strengthen supervision, and foster a safety culture to improve the effectiveness of OSH implementation in construction projects.